1) 4a + 3c – 3a – 4c = а-с
2) 3(3k – c) – (3c - k) = 9к-3с-3с+к= 10к-6с
3) 4(y – a) - 5(2a – y) = 4у-4а-10а+5у= 9у-14а
4) 10 – ( – (2x + 5) – 4) = 10-(2х-5)-4 = 10-2х+5+4 = 19+2х
1) 3y – ( - 4a) + 2y – 3a = 3у+4а+2у= 5у+4а
2) 3(14 – k) – 2(k + 2)= 42-3к-2к-2 = 40-5к
3) 13(a – y) - 12( – y + a) = 13а-13у+12у-а = 12а-у
4) 4 - 2x - (5 – (3x + 2)) = 4-2х-(5-3х-2) = 4-2х-5+3х+2 = 3х+1
1) 4h – 8f + 2f – 12h = -8н-6ф = 8н+6ф
2) 3h – (– 2 + h) - 12 = 3н+2-н-12 = 2н-10
3) - (– 45k + 1) – 2(30k + 5) = 45к-1-60к-10 = -15к-11 = 15к+11
4) x + 2 - (7x – 1 – (x + 2)) = х+2-7х+1+х+2 = -5х+5 = 5х-5